Structural reinvestigation of Li3FeN2: Evidence of cationic disorder through XRD, solid-state NMR and Mössbauer spectroscopy. (August 2016) - Panabière, E.; Emery, N.; Lorthioir, C.; Sougrati, M.T.; Jumas, J.-C.; Bach, S.; Pereira-Ramos, J.-P.; Smith, R.I.; Willmann, P.
Abstract: A significant cationic disorder is evidenced on Li3 FeN2 prepared through solid-state reaction under controlled atmosphere. This derivative anti fluorite type structure (orthorhombic, space group Ibam, a =4.870(1) Å, b =9.652(1) Å and c =4.789(1) Å), solved first through single crystal X-ray diffraction[7], is usually described by Li + and Fe +3 ordered distribution in tetrahedral sites formed by the nitrogen network, leading to [FeN4/2 ] 3− edge-sharing tetrahedral chains. From 7 Li/ 6 Li Nuclear Magnetic Resonance spectroscopy, 57 Fe Mössbauer spectroscopy and powder X-ray and neutron diffraction, we demonstrate that about 4% of lithium sites are filled by iron and about 11% of iron sites are occupied by Li, which can explain the discrepancy within the Gudat's model observed on larger scale solid-state synthesis samples. Highlights: Evidence of cationic disorder in Li3 FeN2 . Crystal structure refinement using powder X-ray diffraction (Rietveld refinement). Number and occupation of lithium environment probed by 6 Li/ 7 Li NMR. Iron environment and oxidation state analyzed by 57 Fe Mössbauer spectroscopy.